P62 Sex differences in primary health care use before and after hospital admission for acute and chronic conditions. A register-based cohort study of the danish population aged 60+. (5th September 2018) - Höhn, A; Gampe, J; Rau, R; Lindahl-Jacobsen, R; Christensen, K; Oksuzyan, A
Abstract : Background: Empirical studies have consistently reported that women have a mortality advantage at all ages as well as with respect to most adverse health conditions and stressful events during the life course. In seeking to explain this advantage, the existing literature has pointed towards the effects and the interactions of biological, behavioral, and social factors. Among the non-biological factors, a large body of previous research has shown that men tend to seek medical help later and less than women, which can lead to delays in diagnosis and treatment. In this study, we explore the sex differences in primary health care use, before and after admission to hospital for chronic and acute conditions to explore whether the sex differences in treatment-seeking behavior change when health worsens. Data: This is a population-based, longitudinal study with nationwide coverage of the population alive and residing in Denmark at age 60+ in 1999. The study population was identified by linking information from the National Health Service Register, the National Patient Register, and the Central Population Register, using a 5% random sample of the Danish population. The study population was followed up for hospital admissions within the period 1999–2008, and GP contacts within the period 1996–2011. We used a generalized additive mixed model (GAMM) to account for repeated observations and to allow non-linear trajectories within the observed period, which covers the three years before and after hospital admission. Results: We found women having consistently more GP contacts than men before and after admission to hospital. The sex differentials in GP contacts were consistently lower for chronic than for acute conditions. For chronic conditions, the sex differentials were small in both periods: while they narrowed in the period before, they were not significant in the period after admission to hospital. For acute conditions, the sex differentials were smaller in the period after admission to hospital when compared with the period before admission to hospital. Conclusion: Our study indicates smaller sex differences in primary health care use following health deterioration, pointing towards a narrowing of the sex differences in treatment-seeking behavior as a result of the presence of symptoms and the experience of a worsening of the health status.